Determination of the Amount of Masterbatch Production Using the Fuzzy-Mamdani Method - Fikri Radiansyah; Wahyu Oktri Widyarto (Universitas Serang Raya, 2019)
Based on demand data from January 2013 to December 2013 at PT. Bukit Surya Mas there is an increase in demand, supply and amount of consumer production every month. With the occurrence of demand, supply and maximum production results PT. Bukit Surya Mas always tries to ensure that the amount of production ordered can be completed on time. This is done as a way to give satisfaction to customers, so that there will be no shortage of production services to consumers just because of the late delivery of the product. Problems that arise in this world often contain uncertainty, fuzzy logic is one method for analyzing systems that contain uncertainty. In this study the Mamdani method or often also known as the Min - Max method. The design of the system to get the output is done in stages (a) the formation of the fuzzy set, (b) the application of the implication function, (c) forming the rules, (d) affirmation (defuzzification). In this study defuzzification was carried out using the centroid method. In this method the defuzzyfication value moves smoothly, so changes in the fuzzy set will also move smoothly. From the results of the research that has been carried out, the following is the Masterbatch product from the input variable in January 2014, namely the total demand of 150,735.00 kg and the total inventory of 24,785 kg resulting in an output of 20,300 units.